Optical sheet, backlight unit, liquid crystal display device, and information device
By strategically placing the antistatic agent in an intermediate layer of the optical sheet, surface contamination from antistatic agents is minimized, ensuring the optical sheet remains clean and bright.
Patent Information
- Application Number
- JP2024174430
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-10
- Filing Date
- 2024-10-03
- Publication Date
- 2025-04-22
AI Technical Summary
Conventional optical sheets used in liquid crystal display devices suffer from surface contamination due to the bleed-out of antistatic agents over time, leading to dirt accumulation and reduced brightness.
The optical sheet is designed with a substrate layer and a coating layer, where the antistatic agent is strategically placed in an intermediate layer between the substrate and the coating layer, with a lower antistatic agent content in the coating layer to prevent surface contamination.
This configuration effectively suppresses surface dirt caused by antistatic agents, maintaining the optical sheet's cleanliness and brightness even under harsh environmental conditions.
Smart Images

Figure 2025066075000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an optical sheet, a backlight unit, a liquid crystal display device, and an information device. [Background technology]
[0002] In recent years, liquid crystal display devices (hereinafter sometimes referred to as LCDs (liquid crystal displays)) have been widely used as display devices for various information devices such as smartphones and tablet terminals. The mainstream backlight units (hereinafter sometimes referred to as BLUs) for LCDs are either the direct type, in which a light source is placed on the back of the liquid crystal panel, or the edge light type, in which a light source is placed near the side of the liquid crystal panel.
[0003] A conventional edge-light type BLU 101 (see Patent Document 1) shown in FIG. 13 includes a light source 102, a rectangular light guide plate 103 arranged so that an end portion of the light guide plate 102 is aligned with the light source 102, a plurality of optical sheets 104 arranged on the front side of the light guide plate 103, and a reflection sheet 105 arranged on the back side of the light guide plate 103. The plurality of optical sheets 104 are a lower light diffusion sheet 106, a prism sheet 107, and an upper light diffusion sheet 108. The lower light diffusion sheet 106 is overlapped on the front side of the light guide plate 103 and has a main light diffusion function. The prism sheet 107 is overlapped on the front side of the lower light diffusion sheet 106, and the upper light diffusion sheet 108, which has a refraction function in the normal direction, is overlapped on the front side of the prism sheet 107 and slightly diffuses light rays to suppress uneven brightness caused by the shape of the prism part of the prism sheet 107, etc.
[0004] The light diffusion sheet generally includes a base layer and a coating layer having a resin matrix and resin beads laminated on the surface side of the base layer. An antistatic agent is added to the coating layer of the light diffusion sheet to prevent the adhesion of dust during the assembly process. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2005-77448 A Summary of the Invention [Problem to be solved by the invention]
[0006] The antistatic performance of the light diffusion sheet is expressed by the bleeding out of the antistatic agent over time. Therefore, depending on the type and amount of the antistatic agent added, there is a problem that foreign matter such as lumps and crystals derived from the antistatic agent may be generated and the sheet surface may become dirty.
[0007] An object of the present disclosure is to provide an optical sheet capable of suppressing surface stains caused by antistatic agents. [Means for solving the problem]
[0008] In order to achieve the above object, the inventors of the present application have conducted extensive research and found that the area ratio of the contaminated area on the surface of the coating layer can be suppressed to less than 20% even when the optical sheet is placed in an environment of 65°C and 95% RH for 48 hours by selecting the type of antistatic agent, adjusting the amount of antistatic agent added, selecting the material of the resin of the coating layer, controlling crosslinking, etc. The inventors of the present application have also found that by providing an intermediate layer containing an antistatic agent between the coating layer and the base layer and making the content of the antistatic agent in the coating layer lower than that of the intermediate layer, it is possible to impart antistatic performance to the optical sheet while suppressing stains on the sheet surface caused by the antistatic agent. The configuration in which the content of the antistatic agent in the coating layer is lower than that of the intermediate layer includes a configuration in which the coating layer does not substantially contain an antistatic agent.
[0009] The optical sheet according to the present disclosure has been made based on the above findings, and specifically, the first optical sheet according to the present disclosure is an optical sheet including a base layer and a coating layer provided on a first surface of the base layer, the coating layer containing an antistatic agent, and when the optical sheet is placed in an environment of 65°C and 95% RH for 48 hours, the area ratio of the contaminated region on the surface of the coating layer is less than 20%. Also, the second optical sheet according to the present disclosure is an optical sheet including a base layer and a coating layer provided on a first surface of the base layer, a first intermediate layer containing an antistatic agent is provided between the base layer and the coating layer, and the content of the antistatic agent in the coating layer is lower than the content of the antistatic agent in the first intermediate layer.
[0010] According to the first optical sheet of the present disclosure, the stains on the sheet surface caused by the antistatic agent can be suppressed with a simple configuration. In the first optical sheet of the present disclosure, when the antistatic agent is an ionic liquid or a reactive emulsifier, the amount of foreign matter such as lumps or crystals caused by the antistatic agent generated can be reduced. In the first optical sheet of the present disclosure, an intermediate layer substantially not containing an antistatic agent may be provided between the base layer and the coating layer.
[0011] According to the second optical sheet of the present disclosure, it is possible to suppress stains on the sheet surface caused by antistatic agents without narrowing the options for the type of antistatic agent that can be used. In the second optical sheet of the present disclosure, the coating layer may not substantially contain an antistatic agent. The first intermediate layer may be an adhesive layer that bonds the base layer and the coating layer. In this case, a second intermediate layer containing an antistatic agent may be provided between the first intermediate layer and the coating layer. Alternatively, in the second optical sheet of the present disclosure, an adhesive layer that does not substantially contain an antistatic agent may be provided between the base layer and the first intermediate layer. In the second optical sheet of the present disclosure, when the half-life of the charging voltage according to the JIS L 1094 A method is 30 seconds or less, sufficient antistatic performance is obtained. In the second optical sheet according to the present disclosure, when the optical sheet is placed in an environment of 65°C and 95% RH for 48 hours, if the contact angle on the surface of the coating layer is reduced by 10 degrees or less, foreign matter such as lumps or crystals derived from the antistatic agent can be suppressed from precipitating on the surface of the coating layer. The second optical sheet according to the present disclosure may further include an anti-sticking layer provided on the second surface of the base layer, the anti-sticking layer being substantially free of an antistatic agent, and a second intermediate layer containing an antistatic agent being provided between the base layer and the anti-sticking layer. Alternatively, the second optical sheet according to the present disclosure may further include an anti-sticking layer provided on the second surface of the base layer, the anti-sticking layer containing an antistatic agent, a second intermediate layer containing an antistatic agent being provided between the base layer and the anti-sticking layer, and the content of the antistatic agent in the anti-sticking layer may be lower than the content of the antistatic agent in the second intermediate layer. When the second optical sheet according to the present disclosure is placed in an environment of 65° C. and 95% RH for 48 hours, the area ratio of contaminated regions on the surface of the coating layer may be less than 20%.
[0012] The backlight unit according to the present disclosure includes a light source and the first or second optical sheet according to the present disclosure. The backlight unit according to the present disclosure includes the first or second optical sheet according to the present disclosure, and therefore can suppress stains on the optical sheet surface caused by the antistatic agent, thereby suppressing a decrease in brightness. In the backlight unit according to the present disclosure, the first or second optical sheet according to the present disclosure may be, for example, a light diffusion sheet.
[0013] The liquid crystal display device according to the present disclosure includes the backlight unit according to the present disclosure and a liquid crystal display panel. Since the liquid crystal display device according to the present disclosure includes the backlight unit according to the present disclosure, it is possible to suppress a decrease in brightness on the display screen.
[0014] The information device according to the present disclosure includes the liquid crystal display device according to the present disclosure. Since the information device according to the present disclosure includes the liquid crystal display device according to the present disclosure, it is possible to suppress a decrease in brightness on the display screen. Effect of the Invention
[0015] According to the present disclosure, it is possible to provide an optical sheet capable of suppressing surface stains caused by antistatic agents. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a backlight unit according to an embodiment. [Diagram 2] 1 is a schematic cross-sectional view showing a light diffusion sheet according to an embodiment of the present invention. [Diagram 3] 1 is a schematic cross-sectional view showing a liquid crystal display device according to an embodiment. [Figure 4] FIG. 11 is a schematic cross-sectional view showing a light diffusion sheet according to Modification 1. [Diagram 5] FIG. 11 is a schematic cross-sectional view showing a light diffusion sheet according to Modification 2. [Figure 6] FIG. 11 is a schematic cross-sectional view showing a light diffusion sheet according to Modification 3. [Figure 7] FIG. 11 is a schematic cross-sectional view showing a light diffusion sheet according to Modification 4. [Figure 8] FIG. 13 is a schematic cross-sectional view showing a light diffusion sheet according to Modification 5. [Figure 9] FIG. 13 is a schematic cross-sectional view showing a light diffusion sheet according to Modification 6. [Figure 10] FIG. 13 is a schematic cross-sectional view showing a light diffusion sheet according to a seventh modified example. [Figure 11] 13 is a schematic cross-sectional view showing a light diffusion sheet according to Modification 8. FIG. [Figure 12] FIG. 13 is a schematic cross-sectional view showing a light diffusion sheet according to a ninth modified example. [Figure 13] FIG. 1 is a schematic perspective view showing a conventional edge-light type backlight unit. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] (Embodiment) Hereinafter, an optical sheet, a backlight unit, a liquid crystal display device, and an information device according to embodiments of the present disclosure will be described with reference to the drawings. Note that the scope of the present disclosure is not limited to the following embodiments, and can be arbitrarily modified within the scope of the technical idea of the present disclosure. In addition, in this disclosure, the "front side" means the viewer side in a liquid crystal display device, and the "rear side" means the opposite.
[0018] <Backlight unit> FIG. 1 is a schematic cross-sectional view showing a backlight unit according to this embodiment, and FIG. 2 is a schematic cross-sectional view showing an upper light diffusion sheet according to this embodiment.
[0019] The backlight unit shown in Figure 1 is an edge-lit backlight unit and includes a light guide sheet 1 that guides light rays incident from an end face to the front surface side, a light source 2 that irradiates light rays toward the end face of the light guide sheet 1, a downward light diffusion sheet 3 superimposed on the front surface side of the light guide sheet 1, a prism sheet 4 disposed on the front surface side of the downward light diffusion sheet 3, an upward light diffusion sheet 5 superimposed on the front surface side of the prism sheet 4, and a reflective sheet 6 disposed on the back surface side of the light guide sheet 1.
[0020] The lower light diffusion sheet 3 diffuses the light rays incident from the back side and focuses them in the normal direction (i.e., focuses and diffuses the light). The prism sheet 4 refracts the light rays incident from the back side in the normal direction. The upper light diffusion sheet 5 slightly diffuses the light rays incident from the back side to suppress brightness unevenness caused by the shape of the prism portion of the prism sheet 4, etc. The reflective sheet 6 reflects the light rays emitted from the back side of the light guide sheet 1 to the front side, allowing them to enter the light guide sheet 1 again.
[0021] <Upper light diffusion sheet> As shown in Figs. 1 and 2, the upper light diffusion sheet 5 is disposed on the surface side of the prism sheet 4, and in this embodiment, in particular, is directly superimposed on the surface of the prism sheet 4 (without any other sheet or the like in between). The upper light diffusion sheet 5 includes a base layer 11 and a coating layer 12 laminated on the surface side of the base layer 11. The coating layer 12 is a light diffusion layer. The upper light diffusion sheet 5 is configured as a two-layer structure of the base layer 11 and the coating layer 12.
[0022] Since the base layer 11 needs to transmit light, it is formed mainly from a transparent (e.g., colorless and transparent) synthetic resin. The main component of the base layer 11 is not particularly limited, and for example, polyethylene terephthalate, polyethylene naphthalate, acrylic resin, polycarbonate, polystyrene, polyolefin, cellulose acetate, weather-resistant vinyl chloride, etc. may be used as the main component of the base layer 11. The "main component" refers to the component with the highest content, for example, a component with a content of 50 mass % or more.
[0023] The lower limit of the average thickness of the substrate layer 11 is preferably about 10 μm, more preferably about 35 μm, and even more preferably about 50 μm. On the other hand, the upper limit of the average thickness of the substrate layer 11 is preferably about 500 μm, more preferably about 250 μm, and even more preferably about 188 μm. If the average thickness of the substrate layer 11 is less than the lower limit, curling may occur when the coating layer 12 is formed by coating. Conversely, if the average thickness of the substrate layer 11 exceeds the upper limit, the brightness of the liquid crystal display device may decrease, and the demand for a thinner liquid crystal display device may not be met. The "average thickness" refers to the average value of thicknesses at any 10 points.
[0024] The coating layer 12 constitutes the outermost surface of the upper light diffusion sheet 5. The coating layer 12 has a resin matrix 13 and resin beads 14 dispersed in the resin matrix 13. The coating layer 12 contains the resin beads 14 dispersed at a substantially uniform density. The resin beads 14 are surrounded by the resin matrix 13. By dispersing the resin beads 14 in the resin matrix 13, minute irregularities are formed on the surface of the coating layer 12, and the irregularities allow the coating layer 12 to diffuse light to the outside. The resin beads 14 may be inorganic particles. As the inorganic particles, for example, inorganic beads such as silica, aluminum hydroxide, aluminum oxide, zinc oxide, barium sulfide, magnesium silicate, or a mixture thereof can be used.
[0025] The lower limit of the average thickness of the coating layer 12 is, for example, about 1 μm, and more preferably about 2 μm. On the other hand, the upper limit of the average thickness of the coating layer 12 is, for example, about 20 μm, and more preferably about 15 μm. If the average thickness of the coating layer 12 is less than the lower limit, the resin beads 14 cannot be reliably fixed by the resin matrix 13, and the resin beads 14 may fall off from the coating layer 12. On the other hand, if the average thickness of the coating layer 12 exceeds the upper limit, it becomes difficult to form minute and high-density unevenness on the surface of the coating layer 12, and as a result, there is a risk that the occurrence of glare caused by interference with the cell arrangement of the liquid crystal panel arranged on the surface side of the upper light diffusion sheet 5 cannot be sufficiently suppressed.
[0026] The resin matrix 13 is formed mainly from a transparent (particularly colorless and transparent) synthetic resin, since it is necessary to transmit light. As the synthetic resin, for example, a thermosetting resin or an active energy ray curable resin can be used. As the thermosetting resin, for example, an epoxy resin, a silicone resin, a phenolic resin, a urea resin, an unsaturated polyester resin, a melamine resin, an alkyd resin, a polyimide resin, an acrylic resin, an amide functional copolymer, a urethane resin, etc. can be used. As the active energy ray curable resin, an ultraviolet ray curable resin that crosslinks and hardens by irradiating ultraviolet rays, an electron beam curable resin that crosslinks and hardens by irradiating electron beams, etc. can be used, and it can be appropriately selected from polymerizable monomers and polymerizable oligomers. In order to improve the adhesion with the substrate layer 11 and prevent the resin beads 14 from falling off the coating layer 12, for example, an acrylic, urethane, or acrylic urethane ultraviolet curable resin can be used as the active energy ray curable resin.
[0027] In this embodiment, an antistatic agent is added to the resin matrix 13. That is, the coating layer 12 contains an antistatic agent. The type of antistatic agent is not particularly limited as long as it does not contain PFAS (organic fluorine compound), and various antistatic agents such as electron conductive type, ion conductive type, and conjugated electron type may be used. Examples of electron conductive antistatic agents include metals and metal oxides such as indium tin oxide (ITO), aluminum-added zinc oxide (ZZAO), and antimony tin oxide. Examples of ion conductive antistatic agents include nonionic types (glycerin fatty acid esters, polyoxyethylene alkyl ether salts, polyoxyethylene alkyl amines, alkyl diethanol amides, etc.), anionic types (alkyl sulfonates, alkyl benzene sulfonates, alkyl phosphates, etc.), cationic types (tetraalkyl ammonium salts, trialkyl benzyl ammonium salts, etc.), and amphoteric types (alkyl pentaines, alkyl imidazolium pentaines, etc.). Examples of the conjugated electron type antistatic agent include polythiophene, polyacetylene, polypyrrole, and polyaniline.
[0028] In this embodiment, the area ratio of the contaminated area on the surface of the coating layer 12 is suppressed to less than 20% even when the upper light diffusion sheet 5 is placed in an environment of 65°C and 95% RH for 48 hours by adjusting the amount of the antistatic agent added, selecting the material of the resin matrix 13, controlling crosslinking, etc., according to the type of the selected antistatic agent. For this purpose, a polymer ion conductive antistatic agent may be used. Examples of the polymer ion conductive antistatic agent include polyether type (polyethylene oxide, polyetheramideimide, etc.), quaternary ammonium salt type (methacrylimide copolymer, maleimide copolymer, etc.), sulfonic acid type (polystyrene sulfonate, etc.), betaine type (carbobetaine graft copolymer, etc.), polymer electrolytic copper conjugate, etc.
[0029] Alternatively, when an ionic liquid such as the AS series manufactured by ADEKA Corporation, or the Elexel (registered trademark) IL or AS series manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd., or a reactive emulsifier such as the ADEKA REASOAP SR, SE, ER or NE series manufactured by ADEKA Corporation is used as the antistatic agent, the amount of foreign matter such as lumps or crystals generated due to the antistatic agent can be particularly reduced.
[0030] The resin matrix 13 may contain additives other than the antistatic agent. Examples of additives that can be used include silicone-based additives and fluorine-based additives. The content of the additives in terms of solid content relative to 100 parts by mass of the synthetic resin component in the resin matrix 13 may be, for example, 0.05 parts by mass or more and 5 parts by mass or less.
[0031] The resin beads 14 are resin particles having the property of transmitting and diffusing light. The resin beads 14 are formed mainly from a transparent, particularly colorless and transparent, synthetic resin. Examples of the main component of the resin beads 14 include acrylic resin, acrylonitrile resin, polyurethane, polyvinyl chloride, polystyrene, polyamide, and polyacrylonitrile. The shape of the resin beads 14 is not particularly limited, and may be, for example, spherical, cubic, needle-like, rod-like, spindle-like, plate-like, scale-like, fibrous, etc., but is preferably spherical, which has excellent light diffusion properties.
[0032] The particle size of the resin beads 14 is preferably as small as possible and equal to or greater than the wavelength of the light irradiated by the light source 2 (hereinafter, sometimes referred to as the light source wavelength), and the upper limit of the average particle size of the resin beads 14 may be, for example, about 2 μm, more preferably about 1 μm. If the average particle size of the resin beads 14 is less than the light source wavelength, the unevenness on the surface of the coating layer 12 becomes too small, resulting in insufficient light diffusion, and there is a risk that the occurrence of uneven brightness due to the shape of the prism parts of the prism sheet 4 cannot be sufficiently suppressed. Conversely, if the average particle size of the resin beads 14 exceeds the upper limit, many relatively large unevennesses are formed on the surface of the coating layer 12, and there is a risk that the occurrence of glare due to interference with the cell arrangement of the liquid crystal panel cannot be sufficiently suppressed.
[0033] The lower limit of the refractive index of the resin beads 14 is, for example, preferably 1.46, and more preferably 1.48. On the other hand, the upper limit of the refractive index of the resin beads 14 is, for example, preferably 1.60, and more preferably 1.59. By setting the refractive index of the resin beads 14 within the above range, the refractive index difference with the resin matrix 13 can be adjusted appropriately (for example, to 0.05 or less), which makes it easier to suppress brightness unevenness caused by the shape of the protruding prism portion of the prism sheet 4. Incidentally, the "refractive index" refers to the refractive index for light with a wavelength of 589.3 nm (the D line of sodium).
[0034] The lower limit of the arithmetic mean roughness Ra of the surface of the coating layer 12 (i.e., the surface of the upper light diffusion sheet 5) may be, for example, about 0.1 μm, more preferably about 0.2 μm. On the other hand, the upper limit of the arithmetic mean roughness Ra of the surface of the coating layer 12 may be, for example, about 1.5 μm, more preferably about 1.0 μm. If the arithmetic mean roughness Ra of the surface of the coating layer 12 is less than the lower limit, the unevenness of the surface of the coating layer 12 becomes too small, resulting in insufficient light diffusion, and the luminance unevenness caused by the shape of the protruding prism portion of the prism sheet 4 may not be sufficiently suppressed. On the other hand, if the arithmetic mean roughness Ra of the surface of the coating layer 12 exceeds the upper limit, many relatively large unevennesses are formed on the surface of the coating layer 12, and the occurrence of glare caused by interference with the cell arrangement of the liquid crystal panel may not be sufficiently suppressed. The "arithmetic mean roughness Ra" refers to a value measured in accordance with JIS B0601-1994.
[0035] The lower limit of the content of the resin matrix 13 in the coating layer 12 may be, for example, about 10% by mass, more preferably about 20% by mass. On the other hand, the upper limit of the content of the resin matrix 13 in the coating layer 12 may be, for example, about 80% by mass, more preferably about 75% by mass. If the content of the resin matrix 13 is less than the lower limit, the light diffusion property of the coating layer 12 may be too high, and the brightness of the liquid crystal display device may not be sufficiently high. On the other hand, if the content of the resin matrix 13 exceeds the upper limit, the number of resin beads 14 in the coating layer 12 may be insufficient, making it difficult to form fine and high-density unevenness on the surface of the coating layer 12, and there is a risk that the occurrence of glare caused by interference with the cell arrangement of the liquid crystal panel arranged on the surface side of the upper light diffusion sheet 5 may not be sufficiently suppressed.
[0036] The lower limit of the content of the resin beads 14 in the coating layer 12 may be, for example, about 20% by mass, more preferably about 25% by mass. On the other hand, the upper limit of the content of the resin beads 14 in the coating layer 12 may be, for example, about 90% by mass, more preferably about 80% by mass. If the content of the resin beads 14 in the coating layer 12 is less than the lower limit, it becomes difficult to form minute and high-density unevenness on the surface of the coating layer 12, and there is a risk that the occurrence of glare caused by interference with the cell arrangement of the liquid crystal panel disposed on the surface side of the upper light diffusion sheet 5 cannot be sufficiently suppressed. On the other hand, if the content of the resin beads 14 in the coating layer 12 exceeds the upper limit, the light diffusion property of the coating layer 12 becomes too high, and the brightness of the liquid crystal display device may not be sufficiently high.
[0037] The lower limit of the haze value of the upper light diffusion sheet 5 may be, for example, about 10%, more preferably about 30%, and even more preferably about 40%. On the other hand, the upper limit of the haze value of the upper light diffusion sheet 5 may be about 90%, more preferably about 70%. If the haze value of the upper light diffusion sheet 5 is less than the lower limit, the brightness unevenness caused by the shape of the protruding prism portion of the prism sheet 4 may not be sufficiently suppressed. Conversely, if the haze value of the upper light diffusion sheet 5 exceeds the upper limit, the brightness of the liquid crystal display device may be insufficient. The "haze value" refers to a value measured in accordance with JIS K 7136:2000.
[0038] <Method of manufacturing the upper light diffusion sheet> The manufacturing method of the upper light diffusion sheet 5 is not particularly limited, but may include, for example, a step of forming a sheet body constituting the base layer 11 (hereinafter referred to as a base layer forming step) and a step of laminating a coating layer 12 on one side of this sheet body (hereinafter referred to as a light diffusion layer lamination step).
[0039] The base layer forming step is not particularly limited, but for example, a method can be used in which a molten thermoplastic resin is extruded from a T-die, and then the extrusion is stretched in the layer longitudinal direction and layer width direction to form a sheet body. For example, a polishing roll method or a chill roll method can be used as a well-known extrusion method using a T-die. In addition, for example, a tubular film biaxial stretching method or a flat film biaxial stretching method can be used as a stretching method for the sheet body.
[0040] The light diffusion layer lamination step may include, for example, a step of preparing a coating liquid containing a resin matrix 13 and resin beads 14 (hereinafter referred to as a preparation step), a step of applying the coating liquid prepared in the preparation step to one side of a sheet body (hereinafter referred to as a coating step), and a step of drying and curing the coating liquid applied in the coating step (hereinafter referred to as a curing step). In the preparation step, a coating liquid containing an active energy ray curable resin as a main component of the resin matrix 13 and also containing the resin beads 14 may be prepared. In the manufacturing method of the upper light diffusion sheet, if an active energy ray curable resin is used as the main component of the resin matrix 13, after the coating liquid is applied in the application step, the active energy ray curable resin can be relatively quickly cured by, for example, irradiating it with ultraviolet light in the curing step. Furthermore, in the preparation step of the manufacturing method of the upper light diffusion sheet, a coating liquid is prepared containing a large amount of resin beads with a small particle size and a small amount of resin beads with a large particle size as the resin beads 14, whereby the small particle size resin beads can suppress the occurrence of glare caused by interference with the cell arrangement of the liquid crystal panel, while the large particle size resin beads can prevent sticking with the liquid crystal panel.
[0041] The manufacturing method of the upper light diffusion sheet 5 may further include a surface treatment step, prior to the light diffusion layer lamination step, of subjecting the surface of the sheet body on which the light diffusion layer is to be laminated to corona discharge treatment, ozone treatment, low-temperature plasma treatment, glow discharge treatment, oxidation treatment, primer coat treatment, undercoat treatment, anchor coat treatment, etc.
[0042] <Prism sheet> Prism sheet 4 is formed mainly from a transparent (e.g., colorless and transparent) synthetic resin since it is necessary to transmit light. Prism sheet 4 has base layer 15 and a protrusion row consisting of a plurality of protruding prism portions 16 laminated on the surface of base layer 15. Protruding prism portions 16 are laminated in a stripe pattern on the surface of base layer 15. Protruding prism portions 16 are triangular prisms whose back surfaces contact the surface of base layer 15.
[0043] The lower limit of the thickness of the prism sheet 4 (the height from the back surface of the base layer 15 to the apex of the protruding prism portion 16) may be, for example, about 50 μm, more preferably about 100 μm. On the other hand, the upper limit of the thickness of the prism sheet 4 may be, for example, about 200 μm, more preferably about 180 μm. The lower limit of the pitch p (see FIG. 2) of the protruding prism portion 16 in the prism sheet 4 may be, for example, about 20 μm, more preferably about 30 μm. On the other hand, the upper limit of the pitch p of the protruding prism portion 16 in the prism sheet 4 may be, for example, about 100 μm, more preferably about 60 μm. The apex angle of the protruding prism portion 16 may be, for example, 85° or more and 95° or less. The lower limit of the refractive index of the protruding prism portion 16 may be, for example, 1.5, more preferably 1.55. On the other hand, the upper limit of the refractive index of the protruding prism portion 16 may be, for example, 1.7.
[0044] The backlight unit of the present embodiment shown in FIG. 1 is not limited to having only one prism sheet 4, and may further have another prism sheet superimposed on the prism sheet 4. In this case, it is preferable that the ridges of the plurality of protruding prism portions 16 of the prism sheet 4 and the ridges of the plurality of protruding prism portions of the other prism sheet are perpendicular to each other. In this way, the light beam incident from the lower light diffusion sheet 3 can be refracted by one prism sheet to the normal direction side, and the light beam emitted from the prism sheet can be refracted by the other prism sheet so as to travel approximately perpendicular to the rear surface of the upper light diffusion sheet 5. The material, thickness, pitch of the protruding prism portions, apex angle of the protruding prism portions, and refractive index of the protruding prism portions of the other prism sheet may be the same as those of the prism sheet 4.
[0045] <Light diffusion sheet for down use> The lower-use light diffusion sheet 3 has a base layer 17, a coating layer 18 disposed on the front side of the base layer 17, and an anti-sticking layer 19 disposed on the back side of the base layer 17. The coating layer 18 is a light diffusion layer and constitutes the outermost surface of the lower-use light diffusion sheet 3. The base layer 17 of the lower-use light diffusion sheet 3 may have a configuration similar to that of the base layer 11 of the above-mentioned upper-use light diffusion sheet 5. The coating layer 18 of the lower-use light diffusion sheet 3 has a light diffusing agent and a binder therefor. The coating layer 18 of the lower-use light diffusion sheet 3 may contain an antistatic agent similar to that of the coating layer 12 of the above-mentioned upper-use light diffusion sheet 5.
[0046] The light diffusing agent used in the coating layer 18 is a particle having a property of diffusing light rays, and is roughly classified into inorganic fillers and organic fillers. As the inorganic filler, for example, silica, aluminum hydroxide, aluminum oxide, zinc oxide, barium sulfide, magnesium silicate, or a mixture thereof can be used. As the organic filler, for example, acrylic resin, acrylonitrile resin, polyurethane, polyvinyl chloride, polystyrene, polyamide, polyacrylonitrile, etc. can be used. The shape of the light diffusing agent is not particularly limited, and may be, for example, spherical, cubic, needle-like, rod-like, spindle-like, plate-like, scale-like, fibrous, etc., but is preferably spherical, which has excellent light diffusing properties.
[0047] The lower limit of the average particle diameter of the light diffusing agent used in the coating layer 18 may be, for example, about 1 μm, more preferably about 2 μm. On the other hand, the upper limit of the average particle diameter of the light diffusing agent may be, for example, about 50 μm, more preferably about 20 μm, and even more preferably about 15 μm. If the average particle diameter of the light diffusing agent is less than the lower limit, the unevenness of the surface of the coating layer 18 may be small, and the light diffusing property required for the lower light diffusing sheet 3 may not be satisfied. On the other hand, if the average particle diameter of the light diffusing agent exceeds the upper limit, the thickness of the lower light diffusing sheet 3 may increase, and uniform diffusion may become difficult.
[0048] The lower limit of the binder content in the coating layer 18 may be, for example, about 15% by mass, more preferably about 30% by mass. On the other hand, the upper limit of the binder content in the coating layer 18 may be, for example, about 48% by mass, more preferably about 45% by mass. If the binder content is less than the lower limit, the light diffusing agent may not be reliably fixed by the binder. Conversely, if the binder content exceeds the upper limit, the light diffusing property may be insufficient.
[0049] The lower limit of the content of the light diffusing agent in the coating layer 18 may be, for example, about 52% by mass, more preferably about 55% by mass. On the other hand, the upper limit of the content of the light diffusing agent in the coating layer 18 may be, for example, about 85% by mass, more preferably about 70% by mass. If the content of the light diffusing agent is less than the lower limit, the light diffusibility may be insufficient. Conversely, if the content of the light diffusing agent exceeds the upper limit, the light diffusing agent may not be reliably fixed by the binder.
[0050] The lower limit of the arithmetic mean roughness Ra of the surface of the coating layer 18 may be, for example, about 0.1 μm, more preferably about 0.2 μm. On the other hand, the upper limit of the arithmetic mean roughness Ra of the surface of the coating layer 18 may be, for example, about 5 μm, more preferably about 3 μm, and even more preferably about 2 μm. If the arithmetic mean roughness Ra of the surface of the coating layer 18 is less than the lower limit, the light diffusibility may be insufficient. Conversely, if the arithmetic mean roughness Ra of the surface of the coating layer 18 exceeds the upper limit, the light transmittance may decrease, and the brightness of the liquid crystal display device may be insufficient.
[0051] The anti-sticking layer 19 is formed by dispersing resin beads in a resin matrix. These resin beads are arranged in a scattered manner on the back surface side of the base layer 17. By arranging the resin beads in a scattered manner, the anti-sticking layer 19 has a plurality of convex portions formed due to the resin beads and a flat portion where no resin beads are present. The anti-sticking layer 19 comes into contact with the light guide sheet 1 arranged on the back surface side in a scattered manner at the plurality of convex portions, but does not come into contact with the entire back surface, thereby preventing sticking and suppressing uneven brightness of the liquid crystal display device.
[0052] The lower limit of the haze value of the lower-use light diffusion sheet 3 may be, for example, about 80%, more preferably about 85%, and even more preferably about 90%. If the haze value of the lower-use light diffusion sheet 3 is less than the lower limit, the light diffusion property may be insufficient. The upper limit of the haze value of the lower-use light diffusion sheet 3 may be, for example, about 95%.
[0053] <Light guide sheet> The light guide sheet 1 is a sheet-like optical member that propagates light emitted from the light source 2 inside and emits it from the surface. The light guide sheet 1 may be formed to have a substantially wedge-shaped cross section, or may be formed to have a substantially flat plate shape. The light guide sheet 1 is formed mainly from a transparent (for example, colorless and transparent) resin, since it is necessary to have light transmissivity. The main component of the light guide sheet 1 is not particularly limited, and may be a synthetic resin such as polycarbonate, which is excellent in transparency and strength, or acrylic resin, which is excellent in transparency and scratch resistance. Since polycarbonate has excellent transparency and a high refractive index, if the main component of the light guide sheet 1 is polycarbonate, total reflection is likely to occur at the interface with the air layer (a layer formed in the gap between the light guide sheet 1 and the lower light diffusion sheet 3, and a layer formed in the gap between the light guide sheet 1 and the reflection sheet 6), and light can be efficiently propagated. In addition, polycarbonate has heat resistance, so that deterioration due to heat generation from the light source 2 is unlikely to occur.
[0054] <Light source> The light source 2 is disposed so that an irradiating surface faces (or abuts) the end face of the light guide sheet 1. Various light sources can be used as the light source 2, for example, a light emitting diode (LED) can be used. Specifically, the light source 2 can be a plurality of LEDs disposed along the end face of the light guide sheet 1.
[0055] <Reflective sheet> The reflective sheet 6 may be, for example, a white sheet having a base resin such as polyester with filler dispersed therein, or a mirror-like sheet having enhanced specular reflectivity by vapor-depositing a metal such as aluminum or silver onto the surface of a film made of polyester or the like.
[0056] <Liquid crystal display device> FIG. 3 is a schematic cross-sectional view showing the liquid crystal display device according to the present embodiment.
[0057] The liquid crystal display device shown in Fig. 3 has a configuration in which a liquid crystal panel 31 is disposed on the front side (front side of the upper light diffusion sheet 5) of the backlight unit shown in Fig. 1. That is, the liquid crystal display device shown in Fig. 3 includes a light guide sheet 1 that guides light rays incident from an end face to the front side, a light source 2 that irradiates light rays toward the end face of the light guide sheet 1, a lower light diffusion sheet 3 superimposed on the front side of the light guide sheet 1, a prism sheet 4 disposed on the front side of the lower light diffusion sheet 3, an upper light diffusion sheet 5 superimposed on the front side of the prism sheet 4, a reflective sheet 6 disposed on the back side of the light guide sheet 1, and a liquid crystal panel 31 superimposed on the front side of the upper light diffusion sheet 5.
[0058] The liquid crystal panel 31 is disposed directly (without any other sheets, etc.) on the surface of the upper light diffusion sheet 5. The liquid crystal panel 31 has a front-side polarizing plate 32 and a back-side polarizing plate 33 disposed substantially parallel to each other with a predetermined gap therebetween, and a liquid crystal cell 34 disposed therebetween. The front-side polarizing plate 32 and the back-side polarizing plate 33 are each composed of a polarizer, such as an iodine-based polarizer, a dye-based polarizer, or a polyene-based polarizer, and a pair of transparent protective films disposed on both sides thereof. The transmission axis directions of the front-side polarizing plate 32 and the back-side polarizing plate 33 are perpendicular to each other.
[0059] The liquid crystal cell 34 has a function of controlling the amount of light transmitted therethrough, and various known liquid crystal cells are used. The liquid crystal cell 34 is generally a laminated structure including a substrate, a color filter, a counter electrode, a liquid crystal layer, a pixel electrode, a substrate, and the like. A transparent conductive film such as ITO is used for the pixel electrode. The display mode of the liquid crystal cell 34 may be, for example, Twisted Nematic (TN), Vertical Alignment (VA), In-Place Switching (IPS), Ferroelectric Liquid Crystal (FLC), Anti-ferroelectric Liquid Crystal (AFLC), Optically Compensatory Bend (OCB), Supper Twisted Nematic (STN), Hybrid Aligned Nematic (HAN), and the like. The pixel pitch of the liquid crystal panel 31 (pixel pitch of the liquid crystal cell) may be, for example, about 25 μm or less.
[0060] <Modification 1 of the upper light diffusion sheet> The upper light diffusion sheet 5 of this modification is different from the upper light diffusion sheet 5 of the embodiment shown in FIG. 2 in that the coating layer 12 does not substantially contain an antistatic agent, and an adhesive layer 21 containing an antistatic agent is provided between the base layer 11 and the coating layer 12 as shown in FIG. 4. That is, the upper light diffusion sheet 5 of this modification is configured as a three-layer structure of the base layer 11, the adhesive layer 21, and the coating layer 12. The adhesive layer 21 is a first intermediate layer. The adhesive layer 21 may contain an antistatic agent similar to that of the coating layer 12 of the embodiment. The adhesive layer 21 may be a primer layer or an easy-adhesive layer that bonds the base layer 11 and the coating layer 12 to which an antistatic agent has been added.
[0061] In the lower light diffusion sheet 3 of the above embodiment (see FIG. 1), the coating layer 18 does not substantially contain an antistatic agent, and an adhesive layer containing an antistatic agent may be provided between the base layer 17 and the coating layer 18, as in this modified example.
[0062] <Modification 2 of the upper light diffusion sheet> The upper light diffusion sheet 5 of this modification is different from the upper light diffusion sheet 5 of the modification 1 shown in FIG. 4 in that, instead of the adhesive layer 21 containing an antistatic agent, the upper light diffusion sheet 5 has an adhesive layer 22 that does not substantially contain an antistatic agent and a thin layer 23 that contains an antistatic agent, as shown in FIG. 5. That is, the upper light diffusion sheet 5 of this modification is configured as a four-layer structure of a base layer 11, an adhesive layer 22, a thin layer 23, and a coating layer 12. The thin layer 23 is a first intermediate layer. The thin layer 23 may contain an antistatic agent similar to the coating layer 12 of the embodiment. The thin layer 23 may be a resin similar to the coating layer 12 of the embodiment to which an antistatic agent has been added.
[0063] In the lower light diffusion sheet 3 of the above embodiment (see FIG. 1), the coating layer 18 does not substantially contain an antistatic agent, and an adhesive layer that does not substantially contain an antistatic agent and a thin layer that contains an antistatic agent may be provided between the base layer 17 and the coating layer 18, as in this modified example.
[0064] <Modification 3 of the upper light diffusion sheet> The upper light diffusion sheet 5 of this modification differs from the upper light diffusion sheet 5 of the modification 1 shown in Fig. 4 in that, as shown in Fig. 6, a thin layer 23 similar to that of the modification 2 is provided between an adhesive layer 21 similar to that of the modification 1 and a coating layer 12. That is, the upper light diffusion sheet 5 of this modification is configured as a four-layer structure of a base layer 11, an adhesive layer 21, a thin layer 23, and a coating layer 12. The adhesive layer 21 is a first intermediate layer, and the thin layer 23 is a second intermediate layer.
[0065] In the lower light diffusion sheet 3 of the above embodiment (see FIG. 1), the coating layer 18 does not substantially contain an antistatic agent, and an adhesive layer and a thin layer each containing an antistatic agent may be provided between the base layer 17 and the coating layer 18, as in this modified example.
[0066] <Modification 4 of the upper light diffusion sheet> The upper light diffusion sheet 25 of this modified example differs from the upper light diffusion sheet 5 of the embodiment shown in Fig. 2 in that a sticking prevention layer 26 is provided on the back surface side of the base material layer 11 as shown in Fig. 7. The upper light diffusion sheet 25 of this modified example shown in Fig. 7 can be applied to the backlight unit shown in Fig. 1 in place of the upper light diffusion sheet 5 of the embodiment. That is, the upper light diffusion sheet 25 of this modified example also slightly diffuses light rays incident from the back surface side to suppress brightness unevenness caused by the shape of the protruding prism portion 16 of the prism sheet 4, and suppresses glare caused by interference with the cell arrangement of a liquid crystal panel (not shown) disposed on the front surface side of the upper light diffusion sheet 25.
[0067] The upper light diffusion sheet 25 of this modified example includes a base material layer 11, a coating layer 12 laminated on the front side of the base material layer 11, and an anti-sticking layer 26 laminated on the back side of the base material layer 11. The upper light diffusion sheet 25 is configured as a three-layer structure of the base material layer 11, the coating layer 12, and the anti-sticking layer 26. The base material layer 11 and the coating layer 12 of the upper light diffusion sheet 25 may be configured similarly to the base material layer 11 and the coating layer 12 of the upper light diffusion sheet 5 of the above embodiment.
[0068] The sticking prevention layer 26 constitutes the back surface of the upper light diffusion sheet 25. The sticking prevention layer 26 is formed mainly from a transparent (e.g., colorless and transparent) synthetic resin because it is necessary to transmit light. The sticking prevention layer 26 is formed in the form of a film having a flat back surface and a substantially uniform thickness. The sticking prevention layer 26 is configured to partially abut against the tops of the protruding prism portions 16 of the prism sheet 4 disposed on the back surface side of the upper light diffusion sheet 25, thereby preventing sticking with the prism sheet 4. Examples of the main component of the sticking prevention layer 26 that can be used include polycarbonate, acrylic resin, polyethylene terephthalate, polyethylene naphthalate, polystyrene, methyl (meth)acrylate-styrene copolymer, polyolefin, cycloolefin polymer, cycloolefin copolymer, cellulose acetate, weather-resistant vinyl chloride, and active energy ray curable resin. In particular, when an acrylic resin is used as the main component of the sticking prevention layer 26, the strength of the back surface of the upper light diffusion sheet 25 is increased, and it becomes easier to prevent the back surface from being scratched.
[0069] The lower limit of the average thickness of the anti-sticking layer 26 may be, for example, about 1 μm, more preferably about 2 μm. On the other hand, the upper limit of the average thickness of the anti-sticking layer 26 may be, for example, about 10 μm, more preferably about 8 μm. If the average thickness of the anti-sticking layer 26 is less than the lower limit, it may not be possible to reliably prevent the rear surface of the upper light diffusion sheet 25 from being scratched. Conversely, if the average thickness of the anti-sticking layer 26 exceeds the upper limit, the brightness of the liquid crystal display device may decrease.
[0070] The upper limit of the arithmetic mean roughness Ra of the back surface of the anti-sticking layer 26 may be, for example, about 0.04 μm, more preferably about 0.035 μm, and even more preferably about 0.03 μm. If the arithmetic mean roughness Ra of the back surface of the anti-sticking layer 26 exceeds the upper limit, the protruding prism portion 16 of the prism sheet 4 may be scratched due to contact with the anti-sticking layer 26. The lower limit of the arithmetic mean roughness Ra of the back surface of the anti-sticking layer 26 is not particularly limited, and may be, for example, 0.01 μm.
[0071] The manufacturing method of the upper light diffusion sheet 25 may include, for example, a step of forming a sheet body constituting the base layer 11 (hereinafter referred to as a base layer forming step), a step of laminating the coating layer 12 on one surface side of the sheet body (hereinafter referred to as a light diffusion layer laminating step), and a step of laminating the anti-sticking layer 26 on the other surface side of the sheet body constituting the base layer 11 (hereinafter referred to as an anti-sticking layer laminating step). As the anti-sticking layer laminating step, for example, a method of forming the anti-sticking layer 26 simultaneously with the sheet body constituting the base layer 11 by a co-extrusion method, a method of laminating the anti-sticking layer 26 by coating on the other surface side of the sheet body, or the like can be used.
[0072] As described above, the base layer forming step in the manufacturing method of the upper light diffusion sheet 25 may be performed simultaneously with the anti-sticking layer lamination step by co-extrusion, or may be performed separately from the anti-sticking layer lamination step. When the base layer forming step and the anti-sticking layer forming step are performed separately, the base layer forming step can be performed in the same manner as the base layer forming step of the upper light diffusion sheet 5 of the above embodiment. Moreover, the light diffusion layer lamination step in the manufacturing method of the upper light diffusion sheet 25 can also be performed in the same manner as the light diffusion layer lamination step of the upper light diffusion sheet 5 of the above embodiment.
[0073] In the upper light diffusion sheet 25 of this modified example, an anti-sticking layer 26 is laminated on the back side of the base material layer 11, so that uneven brightness caused by the shape of the protruding prism portion 16 of the prism sheet 4 can be suppressed, while improving the sticking prevention with the prism sheet 4 and the scratch prevention of the back side of the upper light diffusion sheet 25.
[0074] In the upper light diffusion sheet 25 of this modified example, the anti-sticking layer 26 may contain an antistatic agent similar to that in the coating layer 12 of the above embodiment.
[0075] In the lower light diffusion sheet 3 (see FIG. 1) of the embodiment, the anti-sticking layer 19 may contain an antistatic agent, as in this modification.
[0076] <Modification 5 of the upper light diffusion sheet> The upper light diffusion sheet 5 of this modification is different from the upper light diffusion sheet 5 of the modification 1 shown in FIG. 4 in that, as shown in FIG. 8, an anti-sticking layer 26 similar to that of the modification 4 is provided on the back side of the base layer 11. However, in this modification, the anti-sticking layer 26 does not substantially contain an antistatic agent. In addition, in this modification, an adhesive layer 27 containing an antistatic agent is provided between the base layer 11 and the anti-sticking layer 26. That is, the upper light diffusion sheet 5 of this modification is configured as a five-layer structure of the anti-sticking layer 26, the adhesive layer 27, the base layer 11, the adhesive layer 21, and the coating layer 12. The adhesive layer 27 is a second intermediate layer. The adhesive layer 27 may contain an antistatic agent similar to that of the coating layer 12 of the embodiment. The adhesive layer 27 may be a primer layer or an easy-adhesive layer that bonds the base layer 11 and the anti-sticking layer 26 to which an antistatic agent has been added.
[0077] In the lower light diffusion sheet 3 of the above embodiment (see Figure 1), the coating layer 18 and the anti-sticking layer 19 do not substantially contain an antistatic agent, and adhesive layers containing an antistatic agent may be provided between the base layer 17 and the coating layer 18, and between the base layer 17 and the anti-sticking layer 19, as in this modified example.
[0078] <Modification 6 of the upper light diffusion sheet> The upper light diffusion sheet 5 of this modified example differs from the upper light diffusion sheet 5 of the embodiment shown in Fig. 2 in that, as shown in Fig. 9, an adhesive layer 22 that does not substantially contain an antistatic agent is provided between the base material layer 11 and the coating layer 12. That is, the upper light diffusion sheet 5 of this modified example is configured as a three-layer structure of the base material layer 11, the adhesive layer 22, and the coating layer 12. The adhesive layer 22 is an intermediate layer.
[0079] In the lower light diffusion sheet 3 of the above embodiment (see FIG. 1), the coating layer 18 contains an antistatic agent, and an adhesive layer that does not substantially contain an antistatic agent may be provided between the base layer 17 and the coating layer 18, as in this modified example.
[0080] <Modification 7 of the upper light diffusion sheet> The upper light diffusion sheet 5 of this modification is different from the upper light diffusion sheet 5 of the embodiment shown in FIG. 2 in that, as shown in FIG. 10, an adhesive layer 51 containing an antistatic agent is provided between the base layer 11 and the coating layer 12, and the content of the antistatic agent in the coating layer 12 is lower than the content of the antistatic agent in the adhesive layer 51. That is, the upper light diffusion sheet 5 of this modification is configured as a three-layer structure of the base layer 11, the adhesive layer 51, and the coating layer 12. The adhesive layer 51 is a first intermediate layer. The adhesive layer 51 may contain the same antistatic agent as the coating layer 12 of the embodiment. The adhesive layer 51 may be a primer layer or an easy-adhesive layer that bonds the base layer 11 and the coating layer 12 to which an antistatic agent has been added.
[0081] In the lower light diffusion sheet 3 of the above embodiment (see FIG. 1), the coating layer 18 contains an antistatic agent, and an adhesive layer containing an antistatic agent may be provided between the base layer 17 and the coating layer 18, as in this modified example, and the content of the antistatic agent in the coating layer 18 may be lower than the content of the antistatic agent in the adhesive layer.
[0082] <Modification 8 of the upper light diffusion sheet> The upper light diffusion sheet 5 of this modification is different from the upper light diffusion sheet 5 of the modification 7 shown in FIG. 10 in that, as shown in FIG. 11, an anti-sticking layer 26 similar to that of the modification 4 is provided on the back side of the base layer 11. However, in this modification, the anti-sticking layer 26 does not substantially contain an antistatic agent. In addition, in this modification, an adhesive layer 52 containing an antistatic agent is provided between the base layer 11 and the anti-sticking layer 26. That is, the upper light diffusion sheet 5 of this modification is configured as a five-layer structure of the anti-sticking layer 26, the adhesive layer 52, the base layer 11, the adhesive layer 51, and the coating layer 12. The adhesive layer 52 is a second intermediate layer. The adhesive layer 52 may contain an antistatic agent similar to that of the coating layer 12 of the embodiment. The adhesive layer 52 may be a primer layer or an easy-adhesive layer that bonds the base layer 11 and the anti-sticking layer 26 to which an antistatic agent has been added.
[0083] In the lower light diffusion sheet 3 of the above embodiment (see Figure 1), the coating layer 18 contains an antistatic agent, and the anti-sticking layer 19 does not substantially contain an antistatic agent, and adhesive layers containing an antistatic agent may be provided between the base layer 17 and the coating layer 18, and between the base layer 17 and the anti-sticking layer 19, as in this modified example.
[0084] <Modification 9 of the upper light diffusion sheet> The upper light diffusion sheet 5 of this modification is different from the upper light diffusion sheet 5 of the modification 8 shown in Fig. 11 in that, instead of the anti-sticking layer 26 which does not substantially contain an anti-static agent, an anti-sticking layer 28 containing an anti-static agent is provided, and the content of the anti-static agent in the anti-sticking layer 28 is lower than the content of the anti-static agent in the adhesive layer 52, as shown in Fig. 12. In other words, the upper light diffusion sheet 5 of this modification is configured as a five-layer structure consisting of the anti-sticking layer 28, the adhesive layer 52, the base layer 11, the adhesive layer 51, and the coating layer 12.
[0085] In the lower light diffusion sheet 3 of the above embodiment (see Figure 1), the coating layer 18 and the anti-sticking layer 19 contain an antistatic agent, and adhesive layers containing an antistatic agent may be provided between the base layer 17 and the coating layer 18, and between the base layer 17 and the anti-sticking layer 19, as in this modified example.
[0086] <Features of the embodiment and modifications> The upper light diffusion sheet 5, 25 and the lower light diffusion sheet 3, which are the optical sheets of the embodiment and the modified examples 4 and 6 (hereinafter referred to as the first optical sheet), are optical sheets including a base layer 11, 17 and a coating layer 12, 18 provided on the surface of the base layer 11, 17, and the coating layer 12, 18 contains an antistatic agent, and when the optical sheet is placed in an environment of 65°C and 95% RH for 48 hours, the area ratio of the contaminated area on the surface of the coating layer 12, 18 is less than 20%. The first optical sheet can suppress the stain on the sheet surface caused by the antistatic agent with a simple structure. In the first optical sheet, if the antistatic agent is an ionic liquid or a reactive emulsifier, the amount of foreign matter such as lumps and crystals caused by the antistatic agent can be reduced. In the first optical sheet, an intermediate layer (e.g., an adhesive layer 22) that does not substantially contain an antistatic agent may be provided between the base layer 11, 17 and the coating layer 12, 18.
[0087] The upper light diffusion sheet 5 and the lower light diffusion sheet 3, which are the optical sheets of the above-mentioned modified examples 1 to 3, 5, and 7 to 9 (hereinafter referred to as the second optical sheets), are optical sheets including the base layer 11, 17 and the coating layer 12, 18 provided on the surface of the base layer 11, 17, and a first intermediate layer containing an antistatic agent is provided between the base layer 11, 17 and the coating layer 12, 18, and the content of the antistatic agent in the coating layer 12, 18 is lower than the content of the antistatic agent in the first intermediate layer. According to the second optical sheet, it is possible to suppress the stain on the sheet surface caused by the antistatic agent without narrowing the options such as the type of antistatic agent that can be used. In the second optical sheet, the coating layer 12, 18 may not substantially contain the antistatic agent. Also, the first intermediate layer may be an adhesive layer 21 that bonds the base layer 11, 17 and the coating layer 12, 18. In this case, a second intermediate layer (thin layer) 23 containing an antistatic agent may be provided between the first intermediate layer and the coating layers 12, 18. Alternatively, an adhesive layer 22 containing substantially no antistatic agent may be provided between the base layer 11, 17 and the first intermediate layer in the second optical sheet. In the second optical sheet, if the half-life of the electrostatic voltage according to the JIS L 1094 method A is 30 seconds or less, sufficient antistatic performance is obtained. If the contact angle reduction amount on the surfaces of the coating layers 12, 18 is 10 degrees or less when the second optical sheet is placed in an environment of 65°C and 95% RH for 48 hours, it is possible to suppress the precipitation of foreign matter such as lumps and crystals derived from the antistatic agent on the surfaces of the coating layers 12, 18. The second optical sheet further comprises anti-sticking layers 26, 19 provided on the rear surface of the base material layers 11, 17, and the anti-sticking layers 26, 19 are substantially free of an antistatic agent, and a second intermediate layer (e.g., an adhesive layer 27) containing an antistatic agent may be provided between the base material layers 11, 17 and the anti-sticking layers 26, 19.Alternatively, the second optical sheet may further include anti-sticking layers 28, 19 provided on the back surfaces of the base layers 11, 17, the anti-sticking layers 28, 19 containing an antistatic agent, and a second intermediate layer (e.g., adhesive layer 52) containing an antistatic agent may be provided between the base layers 11, 17 and the anti-sticking layers 28, 19, and the content of the antistatic agent in the anti-sticking layers 28, 19 may be lower than the content of the antistatic agent in the second intermediate layer. When the second optical sheet is placed in an environment of 65°C and 95% RH for 48 hours, the area ratio of contaminated areas on the surfaces of the coating layers 12, 18 may be less than 20%.
[0088] The backlight unit of the above embodiment (including the modified example) includes the light source 2 and the first or second optical sheet, and therefore can suppress staining of the optical sheet surface caused by the antistatic agent, thereby suppressing a decrease in brightness. A liquid crystal display device including this backlight unit and a liquid crystal display panel can suppress a decrease in brightness on the display screen. Similarly, an information device including this liquid crystal display device can suppress a decrease in brightness on the display screen.
[0089] (Example) The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples.
[0090] <Example 1> The optical sheet (lower light diffusion sheet) of Example 1 was manufactured as follows. First, a primer layer made of an acrylic resin and an acrylate resin thermosetting product was provided on the surface of a base layer having an average thickness of 38 μm and mainly composed of polyethylene terephthalate, and a polymeric ion conductive antistatic agent was added to the primer layer. The antistatic agent was Sannol (registered trademark) TD-3130 (polyoxyethylene alkyl (C 13) Sodium ether sulfate) was used. Next, an acrylic resin was wet-coated on the surface of the base layer provided with the primer layer to provide a coating layer with a thickness of 8 μm. A blend of acrylic beads and styrene beads with a particle size of 1 to 15 μm was added to the coating layer, and no antistatic agent was added. Next, a urethane acrylate resin was transferred to the back surface of the base layer to provide an anti-sticking layer with a thickness of 8 μm. No resin beads (light diffusing agent) were added to the anti-sticking layer.
[0091] <Example 2> The optical sheet (lower light diffusion sheet) of Example 2 was manufactured as follows. First, a primer layer made of an acrylic resin and an acrylate resin thermosetting product was provided on the surface of a base layer having an average thickness of 38 μm and mainly composed of polyethylene terephthalate, and a polymeric ion conductive antistatic agent was added to the primer layer. The antistatic agent was Sannol (registered trademark) TD-3130 (polyoxyethylene alkyl (C 13 ) Sodium ether sulfate) was used. Next, an acrylic styrene resin was wet-coated on the surface of the base layer on which the primer layer was provided, to provide a coating layer with a thickness of 10 μm. Acrylic beads with a particle size of 1 to 25 μm were added to the coating layer, and no antistatic agent was added. Next, a urethane acrylate resin was transferred to the back surface of the base layer, to provide an anti-sticking layer with a thickness of 8 μm. No resin beads (light diffusing agent) were added to the anti-sticking layer.
[0092] <Example 3> The optical sheet (lower light diffusion sheet) of Example 3 was manufactured as follows. First, a primer layer made of an acrylic resin and an acrylate resin thermosetting product was provided on the surface of a base layer having an average thickness of 38 μm and mainly composed of polyethylene terephthalate, and a polymeric ion conductive antistatic agent was added to the primer layer. The antistatic agent was Sannol (registered trademark) TD-3130 (polyoxyethylene alkyl (C 13) Sodium ether sulfate) was used. Next, an acrylic styrene resin was wet-coated on the surface of the base layer on which the primer layer was provided, to provide a coating layer with a thickness of 10 μm. Acrylic beads with a particle size of 1 to 25 μm were added to the coating layer, and no antistatic agent was added. Next, a urethane acrylate resin was wet-coated on the back surface of the base layer, to provide an anti-sticking layer with a thickness of 5 μm. Urethane beads with a particle size of 1 to 25 μm were added to the anti-sticking layer, and no antistatic agent was added.
[0093] <Example 4> The optical sheet (upper light diffusion sheet) of Example 4 was manufactured as follows. First, a primer layer made of an acrylic resin and an acrylate resin thermosetting product was provided on the surface of a base layer having an average thickness of 75 μm and mainly composed of polyethylene terephthalate, and a polymeric ion conductive antistatic agent was added to the primer layer. The antistatic agent was Sannol (registered trademark) TD-3130 (polyoxyethylene alkyl (C 13 ) Sodium ether sulfate) was used. Next, a urethane acrylate resin was wet-coated on the surface of the base layer on which the primer layer was provided, to provide a coating layer with a thickness of 5 μm. Acrylic beads with a particle size of 1 to 15 μm were added to the coating layer, and no antistatic agent was added. Next, a urethane acrylate resin was wet-coated on the back surface of the base layer, to provide an anti-sticking layer with a thickness of 8 μm. No resin beads (light diffusing agent) were added to the anti-sticking layer.
[0094] <Reference example> The manufacturing method of the optical sheet (lower light diffusion sheet) of the reference example differs from that of Example 1 in that no antistatic agent was added to the primer layer. That is, the optical sheet of the reference example does not contain an antistatic agent.
[0095] <Comparative Example 1> The manufacturing method of the optical sheet (lower light diffusion sheet) of Comparative Example 1 differs from that of Example 1 in that no antistatic agent was added to the primer layer, but a low molecular weight surfactant acting as an antistatic agent was added to the coating layer. As the antistatic agent, Sanol (registered trademark) EH-1145M (alkyl (C8) sulfate ester MEA salt) manufactured by Lion Corporation was used. The amount of the antistatic agent added was 1.5 parts by mass relative to 100 parts by mass of the constituent resin of the coating layer.
[0096] <Comparative Example 2> The manufacturing method of the optical sheet (lower light diffusion sheet) of Comparative Example 2 differs from that of Example 2 in that no antistatic agent was added to the primer layer, but a low molecular weight surfactant acting as an antistatic agent was added to the coating layer. As the antistatic agent, Sanol (registered trademark) EH-1145M (alkyl (C8) sulfate ester MEA salt) manufactured by Lion Corporation was used. The amount of the antistatic agent added was 1.2 parts by mass relative to 100 parts by mass of the constituent resin of the coating layer.
[0097] <Example 5> The manufacturing method of the optical sheet (lower light diffusion sheet) of Example 5 differs from that of Example 1 in that an antistatic agent is added to the coating layer, not to the primer layer. As the antistatic agent, Sanol (registered trademark) TD-3130 (polyoxyethylene alkyl (C 13 The amount of the antistatic agent added was 1.5 parts by mass with respect to 100 parts by mass of the resin constituting the coating layer.
[0098] <Example 6> The manufacturing method of the optical sheet (lower light diffusion sheet) of Example 6 differs from that of Example 1 in that an antistatic agent is added to the coating layer instead of to the primer layer. As the antistatic agent, Sanol (registered trademark) TD-3130 (polyoxyethylene alkyl (C 13 The amount of the antistatic agent added was 3 parts by mass with respect to 100 parts by mass of the resin constituting the coating layer.
[0099] <Example 7> The manufacturing method of the optical sheet (lower light diffusion sheet) of Example 7 is different from that of Example 1 in that an antistatic agent is added to the coating layer instead of to the primer layer. As the antistatic agent, Sanol (registered trademark) TD-3130 (polyoxyethylene alkyl (C 13 The amount of the antistatic agent added was 5 parts by mass with respect to 100 parts by mass of the resin constituting the coating layer.
[0100] <Evaluation of Examples> For the optical sheets of Examples 1 to 4, Reference Example 1, and Comparative Examples 1 and 2, the electrical resistivity and surface roughness Ra of the sheet surface were measured, a charging voltage test was performed, an ash (ash adhesion) test was performed, the contact angle of the sheet surface was measured, and the occurrence of dirt on the sheet surface was observed. The results shown in Table 1 are the average values for five samples.
[0101] [Table 1]
[0102] The specific details of each measurement and test are as follows. The electrical resistivity was measured in accordance with JIS K 6911 using a flat sample electrode SME-8310 manufactured by Hioki E.E. Corporation, by applying a voltage of 500 V to a 10 cm square area of the measurement sample for 25 seconds, measuring the resistance value, and calculating the electrical resistivity. The surface roughness Ra was measured in accordance with JIS B0601-1994 using a surface roughness tester Surftest SJ-210 manufactured by Mitutoyo Corporation, by contacting the measurement probe with a length of 40 mm on the surface of the measurement sample to measure the surface roughness. The electrostatic charge test was performed in accordance with JIS L 1094 Method B (friction electrostatic charge measurement method) and JIS L 1094 Method A (half-life measurement method) using a friction electrostatic charge tester RST-300A manufactured by Daiei Kagaku Seiki Seisakusho Co., Ltd. (1) The maximum electrostatic charge value was measured when the drum on which the measurement sample was attached was rubbed with a friction cloth conforming to JIS L 0803 #3 for 60 seconds while rotating (400 rpm), (2) the electrostatic charge value was measured 60 seconds after the friction was stopped, and (3) the number of seconds required for the electrostatic charge value to be reduced by half from the maximum electrostatic charge value was measured. In the ash test, the measurement sample was placed on a cloth conforming to JIS L 0803 #3 and rubbed for 5 seconds about 10 times, and then, in a constant temperature and humidity room at 23 ° C and 50% RH, Dabaco ash prepared in advance was brought close to the friction surface of the measurement sample to a distance of 1 cm, and it was examined whether the ash adhered to the measurement sample. For the contact angle measurements, an automatic contact angle meter DMo-601 manufactured by Kyowa Interface Science Co., Ltd. was used to measure the angle of the water droplet (contact angle) 1 second after a 1μg water droplet was dropped onto the sheet surface for each measurement sample before the environmental test (untreated), after the "65°C, 95% RH, 48 hours" environmental test, and after the "85°C, 85% RH, 48 hours" environmental test. For observation of the occurrence of dirt on the sheet surface, three measurement sample optical sheets were stacked, and the "65°C, 95% RH, 48 hours" environmental test was performed, after which a 1.5mm drop was measured at the center of the middle sheet of the three stacked sheets. 2 The area was observed under a microscope at a magnification of 2000 times, and a ratio of the area free of attached matter (contaminants) of 80% or more of the total observed area was marked as ◯, and a ratio of less than 80% was marked as ×. Note that by observing the center sheet of the three stacked sheets, the observation of foreign matter not derived from the antistatic agent, which was generated by direct exposure to the environment, was prevented.
[0103] As shown in Table 1, in Examples 1 to 4 in which no antistatic agent was added to the coating layer, the electrical resistivity of the sheet surface was higher than in Comparative Examples 1 and 2 in which an antistatic agent was added to the coating layer, but the half-life of the electrostatic voltage was 30 seconds or less, and there was almost no ash adhesion in the ash test, so there was no problem with the antistatic performance. On the other hand, in Examples 1 to 4, the stain on the sheet surface caused by the antistatic agent was sufficiently suppressed, whereas in Comparative Examples 1 to 2, the stain on the sheet surface caused by the antistatic agent was not sufficiently suppressed. In addition, as a result of the contact angle test, in Examples 1 to 4, the change (decrease) in the contact angle before and after the environmental test was suppressed to 10 degrees or less, whereas in Comparative Examples 1 to 2, the change (decrease) in the contact angle before and after the environmental test exceeded 20 degrees.
[0104] Moreover, in Examples 5 to 7 in which an antistatic agent was added to the coating layer, antistatic performance was obtained at the same level as in Comparative Examples 1 and 2, and further, when the occurrence of stains on the sheet surface was observed as described above, stains on the sheet surface caused by the antistatic agent were sufficiently suppressed, similar to Examples 1 to 4. That is, when the optical sheets of Examples 5 to 7 were placed in an environment of 65°C and 95% RH for 48 hours, the area ratio of the contaminated region on the surface of the coating layer was less than 20%.
[0105] Additional Examples The present disclosure will be described in further detail below with reference to Examples 8 to 12.
[0106] <Example 8> The optical sheet (lower light diffusion sheet) of Example 8 was manufactured as follows. First, a primer layer composed of an acrylic resin and an acrylate resin thermosetting product was provided on the surface of a base layer having an average thickness of 38 μm and mainly composed of polyethylene terephthalate, and a surfactant-type antistatic agent was added to the primer layer. As the antistatic agent, Sannole (registered trademark) EH-1145M (alkyl (C8) sulfate ester MEA salt) manufactured by Lion Corporation was used. The amount of the antistatic agent added was 1.2 parts by mass per 100 parts by mass of the resin constituting the primer layer. Next, an acrylic styrene resin was wet-coated on the primer layer provided on the surface of the base layer to provide a coating layer with a thickness of 10 μm. Acrylic beads having a particle size of 1 to 25 μm were added to the coating layer, and a polymer ion conductive type antistatic agent was added. As the antistatic agent, Sannole (registered trademark) TD-3130 (polyoxyethylene alkyl (C 13 The amount of the antistatic agent added was 0.5 parts by mass with respect to 100 parts by mass of the resin constituting the coating layer.
[0107] <Example 9> The optical sheet (lower light diffusion sheet) of Example 9 was manufactured as follows. First, a primer layer made of an acrylic resin and an acrylate resin thermosetting product was provided on the surface of a base layer having an average thickness of 38 μm and mainly composed of polyethylene terephthalate, and a polymeric ion conductive antistatic agent was added to the primer layer. The antistatic agent was Sannol (registered trademark) TD-3130 (polyoxyethylene alkyl (C 13) Ether sulfate Na) was used. The amount of the antistatic agent added was 1.5 parts by mass relative to 100 parts by mass of the resin constituting the primer layer. Next, an acrylic styrene resin was wet-coated on the primer layer provided on the surface of the base layer to provide a coating layer with a thickness of 10 μm. Acrylic beads with a particle size of 1 to 25 μm were added to the coating layer, and a surfactant-type antistatic agent was added. As the antistatic agent, Sannole (registered trademark) EH-1145M (alkyl (C8) sulfate ester MEA salt) manufactured by Lion Corporation was used. The amount of the antistatic agent added was 0.5 parts by mass relative to 100 parts by mass of the resin constituting the coating layer.
[0108] <Example 10> The optical sheet (lower light diffusion sheet) of Example 10 was manufactured as follows. First, a first primer layer composed of an acrylic resin and an acrylate resin thermosetting product was provided on the surface of a base layer having an average thickness of 50 μm and mainly composed of polyethylene terephthalate, and a surfactant-type antistatic agent was added to the first primer layer. As the antistatic agent, Sanol (registered trademark) EH-1145M (alkyl (C8) sulfate ester MEA salt) manufactured by Lion Corporation was used. The amount of the antistatic agent added was 1.2 parts by mass with respect to 100 parts by mass of the resin constituting the first primer layer. Next, an acrylic styrene resin was wet-coated on the first primer layer provided on the surface of the base layer, to provide a coating layer with a thickness of 10 μm. Acrylic beads with a particle size of 1 to 25 μm were added to the coating layer, and no antistatic agent was added.
[0109] A second primer layer composed of an acrylic resin and an acrylate resin thermosetting product was provided on the back surface of the base material layer, and a surfactant-type antistatic agent was added to the second primer layer. As the antistatic agent, Sannole (registered trademark) EH-1145M (alkyl (C8) sulfate ester MEA salt) manufactured by Lion Corporation was used. The amount of the antistatic agent added was 1.2 parts by mass per 100 parts by mass of the constituent resin of the second primer layer. Next, a urethane acrylate resin was transferred onto the second primer layer provided on the back surface of the base material layer, and an anti-sticking layer having a thickness of 8 μm was provided. Resin beads (light diffusing agent) and anti-static agent were not added to the anti-sticking layer.
[0110] <Example 11> The optical sheet (lower light diffusion sheet) of Example 11 was manufactured as follows. First, a first primer layer made of an acrylic resin and an acrylate resin thermoset was provided on the surface of a base layer having an average thickness of 50 μm and mainly composed of polyethylene terephthalate, and a polymeric ion conductive antistatic agent was added to the first primer layer. The antistatic agent was Sannol (registered trademark) TD-3130 (polyoxyethylene alkyl (C 13 ) Ether sulfate Na) was used. The amount of the antistatic agent added was 1.5 parts by mass relative to 100 parts by mass of the resin constituting the first primer layer. Next, an acrylic styrene resin was wet-coated on the first primer layer provided on the surface of the base layer to provide a coating layer with a thickness of 10 μm. Acrylic beads with a particle size of 1 to 25 μm were added to the coating layer, and a surfactant-type antistatic agent was added. As the antistatic agent, Sannole (registered trademark) EH-1145M (alkyl (C8) sulfate ester MEA salt) manufactured by Lion Corporation was used. The amount of the antistatic agent added was 0.5 parts by mass relative to 100 parts by mass of the resin constituting the coating layer.
[0111] A second primer layer made of an acrylic resin and an acrylate resin thermosetting material was provided on the back surface of the base material layer, and a polymer ion conductive antistatic agent was added to the second primer layer. The antistatic agent was Sannol (registered trademark) TD-3130 (polyoxyethylene alkyl (C 13 ) Ether sulfate Na) was used. The amount of the antistatic agent added was 1.5 parts by mass relative to 100 parts by mass of the constituent resin of the second primer layer. Next, a urethane acrylate resin was transferred onto the second primer layer provided on the back surface of the base layer to provide an anti-sticking layer with a thickness of 8 μm. No resin beads (light diffusing agent) or antistatic agent was added to the anti-sticking layer.
[0112] <Example 12> The optical sheet (lower light diffusion sheet) of Example 12 was manufactured as follows. First, a first primer layer composed of an acrylic resin and an acrylate resin thermosetting product was provided on the surface of a base layer having an average thickness of 50 μm and mainly composed of polyethylene terephthalate, and a surfactant-type antistatic agent was added to the first primer layer. As the antistatic agent, Sannoru (registered trademark) EH-1145M (alkyl (C8) sulfate MEA salt) manufactured by Lion Corporation was used. The amount of the antistatic agent added was 1.2 parts by mass with respect to 100 parts by mass of the constituent resin of the first primer layer. Next, an acrylic styrene resin was wet-coated on the first primer layer provided on the surface of the base layer to provide a coating layer with a thickness of 10 μm. Acrylic beads with a particle size of 1 to 25 μm were added to the coating layer, and a surfactant-type antistatic agent was added. As the antistatic agent, Sannoru (registered trademark) EH-1145M (alkyl (C8) sulfate MEA salt) manufactured by Lion Corporation was used. The amount of the antistatic agent added was 0.5 parts by mass with respect to 100 parts by mass of the resin constituting the coating layer.
[0113] A second primer layer made of an acrylic resin and an acrylate resin thermosetting material was provided on the back surface of the base material layer, and a polymer ion conductive antistatic agent was added to the second primer layer. The antistatic agent was Sannol (registered trademark) TD-3130 (polyoxyethylene alkyl (C 13 ) ether sulfate Na) was used. The amount of the antistatic agent added was 1.5 parts by mass relative to 100 parts by mass of the constituent resin of the second primer layer. Next, a urethane acrylate resin was transferred onto the second primer layer provided on the back surface of the base layer to provide an anti-sticking layer with a thickness of 8 μm. A surfactant-type antistatic agent was added to the anti-sticking layer. As the antistatic agent, Sannole (registered trademark) EH-1145M (alkyl (C8) sulfate ester MEA salt) manufactured by Lion Corporation was used. The amount of the antistatic agent added was 0.5 parts by mass relative to 100 parts by mass of the constituent resin of the anti-sticking layer. In addition, resin beads (light diffusing agent) were not added to the anti-sticking layer.
[0114] <Evaluation of additional examples> For the optical sheets of Examples 8 to 12, the electrical resistivity of the front and back surfaces of the sheets was measured, a charging voltage test was performed, an ash (ash adhesion) test was performed, and the occurrence of stains on the sheet surface was observed in the same manner as in Examples 1 to 4. The results shown in Table 2 are the average values for five samples.
[0115] [Table 2]
[0116] As shown in Table 2, in Examples 8 to 12, the electrical resistivity of the sheet surface was lower than that of Examples 1 to 4, and the electrical resistivity of the back surface of the sheet was even lower than that of the sheet surface. In addition, in Examples 8 to 12, the half-life of the electrostatic voltage was 10 seconds or less, and there was almost no ash adhesion in the ash test, so there was no problem with the antistatic performance. Furthermore, in Examples 8 to 12, the staining of the sheet surface caused by the antistatic agent was sufficiently suppressed.
[0117] <Layered static charge evaluation> In the manufacturing process of optical sheets, optical sheets cut to a size that can be incorporated into a backlight unit may be transported in a stacked state. If the stacked optical sheets are charged with electricity, it becomes difficult to stack the optical sheets with the edges aligned. Therefore, the inventors of the present application performed the stacking charge evaluation described below for the optical sheets of Examples 1 to 12, Reference Example 1, and Comparative Examples 1 and 2.
[0118] First, three A4-sized optical sheets to be evaluated, a B4-sized flannel cloth attached to a flat plate so as not to cause wrinkles, and an air-blowing static eliminator were prepared. Next, one A4-sized optical sheet was placed on the flannel cloth attached to the plate, and a weight of 500 g was placed on the optical sheet. The flannel cloth and the optical sheet were rubbed 10 times in a circle with a radius of about 100 mm while stacking them in parallel. In this way, a total of three optical sheets were rubbed in order, and the three rubbed optical sheets were stacked. Then, the air-blowing static eliminator was started, and the edge of the topmost one of the three stacked optical sheets was grabbed at a position about 500 mm away from the front of the static eliminator and lifted vertically to a height of 500 mm for about five seconds. Then, when the topmost optical sheet was lifted and the other unclutched optical sheets fell away from the optical sheet (i.e., the optical sheets were not in close contact with each other), it was judged as ○ (best). In addition, when the top optical sheet is lifted, two or more optical sheets including that optical sheet are lifted in close contact, but within 10 seconds, the optical sheets that are not being held separate and fall (when the adhesion of the optical sheets is released by the air blowing from the static eliminator), it was judged as △ (good).In addition, when the top optical sheet is lifted, two or more optical sheets including that optical sheet are lifted in close contact, and the close contact state of the two or more optical sheets is maintained even after 10 seconds, it was judged as × (not good).
[0119] As a result of carrying out the above-described laminated electrostatic evaluation, Examples 1 to 4 were rated △, the Reference Example was rated ×, and Comparative Examples 1 and 2 and Examples 5 to 12 were rated ◯.
[0120] (Other embodiments) Although the embodiments of the present disclosure (including modifications and examples; the same applies below) have been described above, the present disclosure is not limited to the above-described embodiments, and various modifications are possible within the scope of the disclosure. In other words, the description of the above-described embodiments is essentially merely illustrative, and is not intended to limit the present disclosure, its applications, or its uses.
[0121] The optical sheet of the above embodiment may be a two-layer structure of a substrate layer and a coating layer, or a three-layer structure of a substrate layer, a coating layer, and an anti-sticking layer. In addition, another layer such as an intermediate layer may be provided between the substrate layer and the coating layer or between the substrate layer and the anti-sticking layer.
[0122] In the optical sheet of the above embodiment, an antistatic agent is added to the coating layer or to an intermediate layer between the substrate layer and the coating layer, but an antistatic agent may be added to the substrate layer, or an antistatic agent-containing layer may be provided between two substrate layers.
[0123] The backlight unit according to the present disclosure can be embodied in various modified and improved forms in addition to the above-mentioned embodiment. For example, the backlight unit may include other optical sheets other than the upper light diffusion sheet, the prism sheet, and the lower light diffusion sheet on the surface side of the light guide sheet. The backlight unit is not limited to an edge-light type backlight unit, and may be, for example, a direct-type backlight unit in which a diffusion plate and a light source are arranged on the back side of the lower light diffusion sheet. Furthermore, the specific configurations of the prism sheet, light diffusion sheet, light guide sheet, light source, and reflective sheet in the backlight unit are not particularly limited, and various configurations can be adopted. For example, the light diffusion sheet is not limited to a bead-coated type light diffusion sheet, and may be a light diffusion sheet shaped like a pyramid sheet. In these optical sheets of various configurations, an antistatic agent may be contained, as in the optical sheets of the above-mentioned embodiment.
[0124] The backlight unit according to the present disclosure can be used in a wide range of applications, such as relatively large display devices such as personal computers and liquid crystal televisions, mobile phone terminals such as smartphones, and portable information terminals such as tablet terminals.
[0125] In the above embodiment, in the light diffusion sheet including the base layer and the coating layer formed on the base layer, the resin beads are dispersed in the resin matrix of the coating layer which becomes the light diffusion layer to form the uneven shape on the surface of the light diffusion sheet. However, instead of this, for example, the uneven shape may be formed on the surface of the light diffusion sheet by using a mold to which the uneven shape formed by dispersing the resin beads in the resin matrix is transferred, or by using a laser printer device which stores the uneven shape. [Explanation of symbols]
[0126] 1 Light guide sheet 2 light source 3. Lower light diffusion sheet 4 Prism sheet 5. Upper light diffusion sheet 6 Reflective sheet 11 Base material layer 12 Coating Layer 13 Resin matrix 14 Resin beads 15 Base material layer 16 Protruding prism part 17 Base material layer 18 Coating Layer 19 Anti-sticking layer 21 Adhesive layer 22 Adhesive layer 23 thin layer 25 Upper light diffusion sheet 26 Anti-sticking layer 27 Adhesive layer 28 Anti-sticking layer 31 Liquid crystal panel 32 Front side polarizing plate 33 Rear polarizing plate 34 Liquid crystal cell 51 Adhesive layer 52 Adhesive layer
Claims
1. An optical sheet comprising a base layer and a coating layer provided on a first surface of the base layer, The coating layer contains an antistatic agent, When the optical sheet is placed in an environment of 65° C. and 95% RH for 48 hours, the area ratio of contaminated areas on the surface of the coating layer is less than 20%. Optical sheet.
2. An intermediate layer substantially not containing an antistatic agent is provided between the substrate layer and the coating layer. The optical sheet according to claim 1 .
3. An optical sheet comprising a base layer and a coating layer provided on a first surface of the base layer, a first intermediate layer containing an antistatic agent is provided between the substrate layer and the coating layer; the content of the antistatic agent in the coating layer is lower than the content of the antistatic agent in the first intermediate layer; Optical sheet.
4. The coating layer is substantially free of an antistatic agent. The optical sheet according to claim 3 .
5. The first intermediate layer is an adhesive layer that bonds the base material layer and the coating layer. The optical sheet according to claim 3 .
6. A second intermediate layer containing an antistatic agent is provided between the first intermediate layer and the coating layer. The optical sheet according to claim 5 .
7. An adhesive layer substantially not containing an antistatic agent is provided between the base layer and the first intermediate layer. The optical sheet according to claim 3 .
8. The half-life of the charging voltage according to JIS L 1094 Method A is 30 seconds or less. The optical sheet according to claim 3 .
9. When the optical sheet is placed in an environment of 65° C. and 95% RH for 48 hours, the contact angle on the surface of the coating layer is reduced by 10 degrees or less. The optical sheet according to claim 3 .
10. Further comprising an anti-sticking layer provided on the second surface of the base layer, The anti-sticking layer is substantially free of an antistatic agent, A second intermediate layer containing an antistatic agent is provided between the base layer and the anti-sticking layer. The optical sheet according to claim 3 .
11. Further comprising an anti-sticking layer provided on the second surface of the base layer, The anti-sticking layer contains an antistatic agent, a second intermediate layer containing an antistatic agent is provided between the base layer and the anti-sticking layer; the content of the antistatic agent in the anti-sticking layer is lower than the content of the antistatic agent in the second intermediate layer; The optical sheet according to claim 3 .
12. When the optical sheet is placed in an environment of 65° C. and 95% RH for 48 hours, the area ratio of contaminated areas on the surface of the coating layer is less than 20%. The optical sheet according to claim 3 .
13. A light source and the optical sheet according to any one of claims 1 to 12. Backlight unit.
14. A display device comprising the backlight unit according to claim 13 and a liquid crystal display panel. LCD display device.
15. An information device comprising the liquid crystal display device according to claim 14.
Citation Information
Patent Citations
Light diffusing sheet and backlight unit using the same
JP2005077448A